Review Analisa Kondisi Optimum Dalam Proses Pembuatan Biogas - Kurniati, Yuni; Rahmat, Anni; Malianto, Bilal Ivandra; Nandayani, Dita; Pratiwi, Wiwit Sri Werdi (Universitas Trunojoyo Madura, 2021)
Biogas is a gas produced by anaerobic activity with the process of decomposition (degradation) of organic materials. Biogas can be produced from several sources of methane, including domestic (household) waste, biodegradable waste, animal waste, or organic wastes that can be decomposed under anaerobic conditions. This study aims to determine the effect of various conditions (time, pH, stirring time and the type and concentration of inoculum) on biogas production and to analyze the optimum conditions in the biogas production process. This research was conducted with the factors that influence the process of making biogas. Based on the analysis results obtained several processes in the production of biogas, among others, hydrolysis, acetogenesis, asedogenesis, and methanogenesis. The results of the previous experiment were the optimal biogas research from tofu liquid waste, biogas produced with a volume of 26,700 ml, within 36 days and was obtained using an operating temperature of 35-40ᵒC and using cow dung inoculum, and using a 36 liter digester.